2014
DOI: 10.1017/s0029665114000147
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of healthy ageing: expectations and validation

Abstract: The challenge of devising a set of biomarkers capable of measuring the ageing rate in human subjects was articulated long ago. In recent years, progress in the basic biology of ageing suggests the realistic possibility of preventive or restaurative interventions that may extend healthy lifespan in mammals including human subjects. Specifically, frailty is being increasingly recognised as a clinically relevant syndrome that may be therapeutically addressed. This greatly enhances the need for sensitive and speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 94 publications
(133 reference statements)
0
26
0
1
Order By: Relevance
“…Such understanding cannot simply be extrapolated from results obtained in younger populations because the power of biomarkers to predict the impact of various pathophysiological mechanisms on successful ageing is frequently dependent on age itself ( Martin-Ruiz and von Zglinicki, 2014 ). For late nonagenarians and centenarians, some relatively small studies have shown improved or at least well maintained levels of certain biomarkers including immunosenescence markers ( Strindhall et al, 2007 ) but data on telomere length, a prominent marker of cell senescence, were contradictory in this age group ( Atzmon et al, 2010 , Kimura et al, 2007 , Tedone et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Such understanding cannot simply be extrapolated from results obtained in younger populations because the power of biomarkers to predict the impact of various pathophysiological mechanisms on successful ageing is frequently dependent on age itself ( Martin-Ruiz and von Zglinicki, 2014 ). For late nonagenarians and centenarians, some relatively small studies have shown improved or at least well maintained levels of certain biomarkers including immunosenescence markers ( Strindhall et al, 2007 ) but data on telomere length, a prominent marker of cell senescence, were contradictory in this age group ( Atzmon et al, 2010 , Kimura et al, 2007 , Tedone et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…A biomarker for ageing can be conservatively defined as “a biological parameter of an organism that either alone or in some multivariate composite will, in the absence of disease, better predict functional capacity at some late age than will chronological age” (Baker and Sprott, 1988, Martin-Ruiz and von Zglinicki, 2014). Ideal biomarkers must also be simple and uninvasive to assess (i.e.…”
Section: Biomarkers For Detecting Drug Efficacy Against Ageingmentioning
confidence: 99%
“…Table 2 summarizes some of the studies carried out focusing on the changes of the transcriptome during aging, in humans. Such studies, however, are usually based on a small set of samples, as it can be quite difficult to obtain adequate tissues for analysis in human studies, thus significantly impairing not only their power of discovery, but of validation as well [56,57]. For studies focusing on larger samples, the biofluid of choice is, mostly, blood, which is easily accessible.…”
Section: Transcriptomicsmentioning
confidence: 99%
“…Table 4 highlights some of these studies and describes the key findings of each experimental work. (Table 4), but, in many cases, their variability in cross-sectional studies is considerable and, consequently, none has emerged as an useful marker to independently determine biological age [57], particularly in large cohorts of human population(s) [129]. This may be due not only to the inherently multi-causal and multi-system nature of the aging process, but also to the frequently concomitant age-related illnesses.…”
Section: Metabolomicsmentioning
confidence: 99%